2006
DOI: 10.1111/j.1463-1318.2006.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term cancer risk of the anorectal cuff following restorative proctocolectomy assessed by p53 expression and cuff dysplasia

Abstract: The lack of carcinoma and dysplasia in the columnar cuff epithelium specimens is reassuring. The lack of stabilized p53 and absence of a relationship between p53 stabilization and dysplasia up to 12 years after pouch formation suggests neoplastic transformation is a rare event. Furthermore, p53 expression was not useful in surveillance of cuff biopsies from patients who have undergone RP for UC and the search should continue for alternative predysplastic markers. These data suggest that in patients who do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…They state that DNA labeling index, overexpression of p53, and aneuploidy determination have better sensitivity. On the other hand, a recent long-term follow-up study of dysplasia in patients with IPAA for UC found p53 overexpression to be a nonspecific marker of malignancy [19]. Therefore, histopathology remains the gold standard for dysplasia and malignancy surveillance in patients with IPAA for UC, at least until cost-effective alternative or complementary immunohistochemical or biomarkers are available.…”
Section: Discussionmentioning
confidence: 97%
“…They state that DNA labeling index, overexpression of p53, and aneuploidy determination have better sensitivity. On the other hand, a recent long-term follow-up study of dysplasia in patients with IPAA for UC found p53 overexpression to be a nonspecific marker of malignancy [19]. Therefore, histopathology remains the gold standard for dysplasia and malignancy surveillance in patients with IPAA for UC, at least until cost-effective alternative or complementary immunohistochemical or biomarkers are available.…”
Section: Discussionmentioning
confidence: 97%
“…Controversy surrounds the role of p53. Coull et al found no correlation between ATZ dysplasia and overexpression of p53 (affecting one in two patients) [159]. On the contrary, other studies have highlighted a link between over-expressed p53 and aneuploidy, dysplasia and pouch cancer [160,161].…”
Section: Underlying Mechanismsmentioning
confidence: 96%
“…It is commonly believed that a history of colorectal cancer, the presence of "backwash ileitis" and the co-existence of primary sclerosing cholangitis are significant independent risk factors for malignant transformation in the "neorectum" [24]. Some authors suggest that a malignancy developing in an intestinal pouch may in fact be cancer of ileal-anal anastomosis originating from the remaining "cuff" of rectal mucosa [28,29]. Jiang et al describe the features of 12 cases of pouch and peripouch adenocarcinoma, and there was just 1 in the pouch only; 8 in the anal transitional zone (ATZ, defined as the part of the rectum between the dentate line and anastomosis); 2 in the ATZ and pouch; and 1 in a nonspecific peripouch region [26] In the present study, in addition to the clinical, endoscopic and histological evaluation of intestinal pouches, a microbiological assessment of material collected from pouch lumen was performed.…”
Section: Discussionmentioning
confidence: 99%